WATER WAVE AND ENERGY GENERATOR - MOHAMED YOUSUFF, FARWIZAH (Universiti Teknologi PETRONAS, 2016)
Piezoelectric unit create energy through adding mass and by varying frequencies. Mechanical stress on piezoelectric produces energy simply by those two variables. However, piezoelectric is prone to extreme mechanical stress and it can onlyproducelow amount of energy due to low frequency. This research aims to enhance the output byminimizing the loss by considering NPN bipolar power transistor, and ultracapacitor. Piezoelectric unit is tested in the vibration lab by attaching it to a shaker. The shaker isthen set to 5 different sets of frequencies, starting from 0 Hz to 50 Hz. Readingsofcurrent and voltages is taken. Same procedure is repeated but with different sets of mass, ranging from 0 to 30 grams. The results shows that the increasing mass and frequencygives positive increment to both voltage and current. As conclusion, it is shown that increasing mass and frequencies produces positiveandincreasing power.